Evaluation of Small Molecules as Front Cell Donor Materials for High‐Efficiency Tandem Solar Cells. Issue 32 (23rd May 2016) - Zhang, Qian; Wan, Xiangjian; Liu, Feng; Kan, Bin; Li, Miaomiao; Feng, Huanran; Zhang, Hongtao; Russell, Thomas P.; Chen, Yongsheng
Abstract : Three small molecules as front cell donors for tandem cells are thoroughly evaluated and a high power conversion efficiency of 11.47% is achieved, which demonstrates that the oligomer‐like small molecules offer a good choice for high‐performance tandem solar cells.